2020
DOI: 10.1177/2045894020968531
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic profiles in pulmonary arterial hypertension associate with disease severity and identify novel candidate genes

Abstract: Using RNAseq, we identified a 61 gene-based circulating transcriptomic profile most correlated with four indices of pulmonary arterial hypertension (PAH) severity. In an independent dataset, 13/61 (21%) genes were differentially expressed in lung tissues of PAH cases versus controls, highlighting potentially novel candidate genes involved in PAH development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…The correlations between gene and clinical features observed in the discovery cohort were also examined in our validation cohort of 91 subjects, and also in an external cohort of 32 subjects with RNA collected from PBMCs 26 . We found that 64 of the 90 (71%) correlations measured in these two independent cohorts were consistent with our discovery cohort (Supplementary Table 5 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The correlations between gene and clinical features observed in the discovery cohort were also examined in our validation cohort of 91 subjects, and also in an external cohort of 32 subjects with RNA collected from PBMCs 26 . We found that 64 of the 90 (71%) correlations measured in these two independent cohorts were consistent with our discovery cohort (Supplementary Table 5 ).…”
Section: Resultsmentioning
confidence: 99%
“…The cohort comprised 84 subjects with Group 1 PAH of whom 32 were diagnosed with idiopathic PAH. For each subject, demographics and clinical variables were collected 26 . PBMCs were stored in RNAlater as previously described.…”
Section: Methodsmentioning
confidence: 99%
“…The GSE117261 dataset (containing lung samples from 58 PAH patients and 25 healthy controls) was obtained from the GEO database ( https://www.ncbi.nlm.nih.gov/geo/ ) and analyzed accordingly [ 22 ]. The expression matrix was annotated with GPL6244, Affymetrix human gene 1.0 ST array (transcription/gene), and normalized using the limma software package and the ‘quantify’ method [ 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…Microarray expression data (GSE117261) [ 9 , 10 ] was downloaded from the Gene Expression Omnibus (GEO) database ( https://www.ncbi.nlm.nih.gov/geo/ ), representing a GPL6244 Affymetrix Human Gene 1.0 ST Array. GSE117261 includes 57 lung tissue specimens from 32 PAH patients and 25 normal controls.…”
Section: Methodsmentioning
confidence: 99%
“…Microarray expression data (GSE117261) [9,10] was downloaded from the Gene Expression Omnibus (GEO) database (https:// www. ncbi.…”
Section: Data Sourcesmentioning
confidence: 99%